Necrotizing Soft Tissue Infection (NSTI) of Head and Neck: A Case Report - Moksidy, Reynaldy C.; Oley, Mendy Hatibie; Tamburian, Christa; Suoth, Stevy (Universitas Batanghari Jambi, 2025)
Necrotic soft tissue infection (NSTI) is a rapidly progressing skin infection characterized by necrosis of the fascia and subcutaneous tissue, while Ludwig's angina is a severe connective tissue infection of the floor of the mouth, often a complication of a dental infection, which can cause upper airway obstruction if left untreated. This study presents the case of a 32-year-old female patient with no previous hospitalization who presented to the Emergency Room with a wound and pain radiating from the neck to the chest, lasting for one week. The patient underwent a standard diagnostic and therapeutic protocol, including aggressive debridement under general anesthesia, with skin preservation and reconstruction via partial-thickness skin graft (STSG) for the wound defect. Ludwig's angina is primarily caused by infection of the mandibular molars, particularly the second and third molars, which account for more than 90% of cases. Although relatively rare, NSTI is characterized by rapid necrosis of the fascia and subcutaneous fat, leading to skin necrosis. Vigilance for the development of complications from cellulitis to NSTI, especially in cases thought to be caused by Ludwig's angina, is essential. Factors such as potential window periods for HIV and malnutrition need to be considered, emphasizing the importance of collaboration between reconstructive surgery specialists, epidemiologists, and thoracic and vascular disciplines to improve treatment strategies and preventive measures.